2014
DOI: 10.1246/cl.131124
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Rutile Titania for Hydrogen Evolution

Abstract: Herein, we demonstrate the high photocatalytic activity of rutile particles for H 2 evolution from aqueous ethanol solution. The rutile particles were prepared by successive calcination at 900°C and H 2 reduction treatment at 700°C of commercial anatase-rich TiO 2 powder, Evonik/Degussa P25. Photocatalytic water splitting to generate H 2 and O 2 using oxide photocatalysts has potential for large-scale fuel production from solar energy.1 Titanium dioxide has been a widely studied photocatalyst since the photoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
2
17
1
Order By: Relevance
“…Contrary to this viewpoint, we demonstrated that H 2 -reduced rutile TiO 2 is much more active than mixed-phase P25 for photocatalytic H 2 evolution from aqueous ethanol solution [17,18]. To confirm that the anatase phase does not work as an active component, we investigated H 2 reduction treatment of pure single-phase rutile particles [17]. P25 was first calcined in air at 900 C to induce complete phase transition from anatase to rutile, and then the pure rutile phase was reduced by H 2 at 700 C( Figure 7A).…”
Section: Reduced Tio 2 With Pure Rutile Phasecontrasting
confidence: 80%
See 1 more Smart Citation
“…Contrary to this viewpoint, we demonstrated that H 2 -reduced rutile TiO 2 is much more active than mixed-phase P25 for photocatalytic H 2 evolution from aqueous ethanol solution [17,18]. To confirm that the anatase phase does not work as an active component, we investigated H 2 reduction treatment of pure single-phase rutile particles [17]. P25 was first calcined in air at 900 C to induce complete phase transition from anatase to rutile, and then the pure rutile phase was reduced by H 2 at 700 C( Figure 7A).…”
Section: Reduced Tio 2 With Pure Rutile Phasecontrasting
confidence: 80%
“…The mixture of anatase and rutile phases in P25 is reportedly more active than the individual polymorphs of TiO 2 . Contrary to this viewpoint, we demonstrated that H 2 -reduced rutile TiO 2 is much more active than mixed-phase P25 for photocatalytic H 2 evolution from aqueous ethanol solution [17,18]. To confirm that the anatase phase does not work as an active component, we investigated H 2 reduction treatment of pure single-phase rutile particles [17].…”
Section: Reduced Tio 2 With Pure Rutile Phasementioning
confidence: 85%
“…As displayed in Fig. 6, the performance of the photocatalytic water oxidation for O 2 evolution was achieved when the ratio between anatase and rutile crystalline phases are superior (88%, Table 1), corroborating with the reported investigations 33,34 .…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, for the synthesised TiO 2 calcined at 900 ºC 100% rutile (Table 1) the performance for O 2 production was lower compared with the TiO 2 -700 and also with TiO 2 -800 samples, suggesting that the other factors account to the e ciency of the process using the TiO 2 samples prepared by sol-gel method. As documented, the ratio between surface anatase and rutile particles increases the photocatalytic activity in water splitting reactions 32,33 . As displayed in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Amano et al. reported that H 2 ‐reduced rutile TiO 2 was much more active than mixed‐phase P25 for photocatalytic H 2 evolution under ultraviolet irradiation . The AQY for H 2 evolution of H 2 ‐reduced rutile TiO 2 was 46 % under 390 nm irradiation .…”
Section: Overall Water Splitting Into H2 and O2 Over Rutile Tio2 Photmentioning
confidence: 99%